1999
DOI: 10.1002/(sici)1099-0496(199907)28:1<3::aid-ppul2>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled nitric oxide, oxygen, and alkalosis: Dose-response interactions in a lamb model of pulmonary hypertension

Abstract: Inhaled nitric oxide (NO) is currently used as an adjuvant therapy for a variety of pulmonary hypertensive disorders. In both animal and human studies, inhaled NO induces selective, dose‐dependent pulmonary vasodilation. However, its potential interactions with other simultaneously used pulmonary vasodilator therapies have not been studied. Therefore, the objective of this study was to determine the potential dose‐response interactions of inhaled NO, oxygen, and alkalosis therapies. Fourteen newborn lambs (age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 45 publications
1
12
1
Order By: Relevance
“…This contrasts with a recent study showing that acute alkalosis enhanced iNO-induced pulmonary vasodilation in intact lambs. 25 Several factors may contribute to the discordant effects of acute and sustained alkalosis on both pulmo-nary vasoconstriction and vasodilation. For example, acute alkalosis-induced pulmonary vasodilation appeared to be mediated by endothelium-derived nitric oxide, 14,23 PGI 2 , 11,13,22 or K + channel activity 24 in various studies, and increases in these modulators might well enhance the vasodilatory effects of exogenous iNO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This contrasts with a recent study showing that acute alkalosis enhanced iNO-induced pulmonary vasodilation in intact lambs. 25 Several factors may contribute to the discordant effects of acute and sustained alkalosis on both pulmo-nary vasoconstriction and vasodilation. For example, acute alkalosis-induced pulmonary vasodilation appeared to be mediated by endothelium-derived nitric oxide, 14,23 PGI 2 , 11,13,22 or K + channel activity 24 in various studies, and increases in these modulators might well enhance the vasodilatory effects of exogenous iNO.…”
Section: Discussionmentioning
confidence: 99%
“…20 However, acidosis increased both baseline and hypoxic PVR in several animal 14,21 and human 15 studies. Thus, vasodilator thelium-derived and endothelium-independent modulator activity 11,13,[22][23][24] and inhaled nitric oxide (iNO)-induced pulmonary vasodilation, 25 suggesting that sustained alkalosis may also potentiate subsequent endotheliumdependent and -independent pulmonary vasodilation. However, alkalosis has also been found to enhance systemic and pulmonary vascular smooth muscle contractility [26][27][28][29] and, in contrast to acute alkalosis, sustained alkalosis failed to attenuate pulmonary vasoconstriction in several preparations.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously demonstrated increased pulmonary vasoconstriction in shunted lambs. 17,26,33,34 Therefore, it is notable that we found persistently elevated cGMP levels at each age point in shunted lambs as compared to normal lambs since cGMP results in pulmonary vascular smooth muscle cell relaxation. Our data suggest that by 4 weeks of age BNP may contribute significantly to cGMP levels in shunted lambs.…”
Section: Discussionmentioning
confidence: 64%
“…A 1999 study by Heidersbach and colleagues demonstrated dose-dependent pulmonary vasodilation in a lamb model in response to oxygen, alkalosis, and iNO. They proceeded to demonstrate that when the therapies were used in combination, a systemic arterial pH > 7.40 augmented iNO-induced pulmonary vasodilation [10]. The present review was undertaken to examine the validity of the empiric observation that many babies with PPHN continue to exhibit pH-responsiveness when receiving treatment with iNO.…”
Section: Discussionmentioning
confidence: 99%